The Power of Price and Promotion in Stimulating Consumer Purchase Decisions: A Study on HMNS Perfume - Dharmawan, Ikke Putri; Moko, Wahdiyat (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the influence of price and promotion on the purchase decision of HMNS perfume among students in Malang City. The independent variables in this study include price and promotion, while the dependent variable is the purchase decision. The study employs a quantitative approach using an online survey method. The sample consists of 100 respondents selected using the purposive sampling technique. The results of multiple linear regression analysis indicate that price and promotion have a significant influence on purchase decisions. Specifically, price shows a positive and significant relationship, suggesting that the alignment of price with product quality are important factors for consumers. Promotion also plays a significant role, particularly through marketing strategies such as discounts and social media. This research provides practical contributions to HMNS in understanding the factors influencing consumer purchase decisions, particularly in the student segment. Marketing strategies involving competitive pricing, attractive promotions, and leveraging impulsive buying behavior can enhance sales performance. Theoretically, this study enriches the literature on consumer behavior and purchase decisions in Indonesia's local perfume industry